Pengaruh CAR, LDR, BOPO, dan Size Terhadap ROA pada Sektor Perbankan yang Terdaftar di BEI 2015-2019 - Dwi Kumala Safitri Agam; Gatot Heru Pranjoto (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The research approach used in this research is descriptive and quantitative. Sampling using Purposive Sampling method and obtained samples as many as 41 banking companies. The data analysis technique used is multiple linear regression analysis. The results of the T Test analysis showed that the variable Capital Adequacy Ratio (CAR) and Company Size (Size) had a positive and significant effect. The results of the T Test analysis showed that the Variable Loan to Deposit Ratio (LDR) had a positive and insignificant effect. Operating Income Operating Expenses (BOPO) have a negative and insignificant effect. The ability to explain from the four independent variables to Profitability (ROA) is 77,9% indicated by the size of Adjusted R Square, the remaining 22,1% is explained by other variables outside this research model.